Acupoint Massage in Improving Sleep Quality of Older Adults - Reza Hossein-Abadi; Kian Nowrouzi; Reza Pouresmaili; Masoud Karimloo; Sadat Seyyed Bagher Maddah (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: Elderly people often suffer from disturbed sleep and Traditional Chinese acupressure is a noninvasive technique that employs pressure and massage to acupoints in order to stimulate the balance of life energy that promotes health and comfort. The purpose of present study was to determine the effectiveness of acupoints massage in elders experiencing sleep disturbances. Materials & Methods: In this quasi experimental study which was applied as single blind clinical trial, Pittsburgh Sleep Quality index (PSQI) questionnaire was used as a screening tool to select individuals with sleep disturbance by purposeful sampling. Then the individuals were assigned to three groups by balanced randomized method (an acupressure group, a sham acupressure group and control group). Each group had 30 subjects and gender ratio was equal in three groups. The same massage was used in the acupressure group and the sham acupressure group, whereas only conversation was employed in the control group. Time of interventions was limited to 15 min. One course of intervention lasted for 3 days per week. These interventions were carried out for 4 consecutive weeks. After intervention 77 persons completed the questionnaire. Repeated measure ANOVA, ANCOVA and Kruskal-Wallis tests were used for data analysis. Results: The analysis of data post intervention showed significant differences in PSQI subscale scores of the subjective sleep quality (P=0.025), sleep duration (P=0.012), sleep efficiency (P=0.022), sleep disturbance (P=0.025), daily performance (P=0.033), sleep latency (P<0.001) and global PSQI scores (P<0.001) among three groups. POST HOC comparison showed significant differences in PSQI subscales scores and global PSQI scores in the acupressure group compared to control group (P<0.05). Whereas, there was significant difference only in PSQI subscales scores of the sleep latency (P=0.006) and global PSQI scores (P=0.021) in the acupressure group compared to the sham acupressure group. Sleep log data showed significant decrease of awake time and improving the quality of sleep in acupressure group (P<0.001). Conclusion: This study confirmed the effectiveness of acupressure in improving the quality of sleep of elderly people and offered a nonpharmacological therapy method for sleep-disturbed elderly people.